The impact of the coronavirus pandemic on advertising communication of brands in the outdoor space. Real-time marketing in practice - Rakoczy, Anna (Linguistic creativity in marketing, 2022)
The widespread pandemic that companies and the brands under their care had to deal with, had an impact not only on changes in management, HR and financial processes. It touched equally heavily in areas related to the implementation of marketing strategies, communication with recipients and advertising messages. Many brands resigned from the campaigns conducted so far and decided to apply solutions typical of real-time marketing, which in practice meant adapting in terms of persuasion and language to the circumstances of the ongoing pandemic in order to establish the expected agreement with preferred recipients and influence their purchasing decisions or to elicit a different kind of involvement. The aim of the article is to analyze - both graphically and linguistically - the observed impact of the coronavirus pandemic on the advertising communication of selected brands based on their advertising creations. In order to standardize and narrow down the material being the subject of the analysis, only those advertisements that appeared in the outdoor space (both single and part of more complex campaigns) were included in the research body. The leitmotif of the text is the thesis that public space, in the era of new restrictions imposed on society, including mobility, has become a special place where the outdoor message gained importance and had a chance to make an exceptionally strong impression on the recipients.